Pulmonary Arterial Hypertension: Molecular Genetic Basis and Emerging Treatments - Siddiqui, MA; Ogo, Takeshi; Nasim, MT (Anwer Khan Modern Medical College Journal, 2012)
Pulmonary arterial hypertension (PAH) is a rare cardiovascular disorder caused by narrowing of blood vessels in the lung and in the absence of therapy leads to right heart failure and death. No cure for this devastating disorder is known. The major objective of the current treatments is to improve symptoms and these therapies were developed prior to the discovery that this disease has substantial genetic components. In this review, we discuss molecular genetic basis of PAH together with pathobiology, current and future therapeutic interventions. DOI: http://dx.doi.org/10.3329/akmmcj.v3i2.11691 AKMMC J 2012; 3(2): 30-33